The Unregulated Domain: The Absence of Islam in the 1681 Alliance Treaty between Cirebon and the Dutch East India Company - Satrio Dwicahyo (Tashwirul Afkar, 2021)
Islam has always been the fulcrum of Cirebon courts. The centrality of Islam in the courts’ politics and culture is apparent today as it was in the seventeenth century. The last three decades of the seventeenth century were crucial for Cirebon since the formerly unitary sultanate of Cirebon (or Pakungwati) experienced a trifurcation. Subsequently, the new Cirebon rulers consisted of two sultans and one lord (panembahan) made a breakthrough by signing an alliance treaty with the Dutch East India Company (or VOC). Both parties signed the first treaty in 1681, which consensually confined the three rulers from exercising “real” powers. Although Islam is the core of Cirebon’s power, it was missing from both the negotiation and the final draft of the 1681 treaty. The present study, therefore, will unravel the arguments behind the “absence” of clauses that regulate Cirebon rulers’ religious exercise from the treaty that aims to limit their power. In so doing, this study accesses the combination of Dutch primary sources (VOC documents) with Cirebon local sources (Babad, Naskah, among others). Preliminary findings of the present study indicate that Cirebon and VOC shared different notions of power. Although VOC recognizes Cirebon’s priesthood, the company showed no interest in regulating the aspect that did not significantly influence them.